Sistema de Laboratorios Remotos para la práctica de Ingeniería de Control - Mar-Cornelio, Omar; Santana-Ching, Iván; González-Gulín, Jorge (Revista Científica, 2019)
For the development of laboratory practices, students work in physical devices or remotely, in person or remotely using Remote Laboratory Systems (SLR). However, current solutions do not have support or are proprietary, making it impossible to implement them for the development of Control Engineering practices in the Cuban Educational System. The present investigation describes a solution to the problematic one raised from the development of a System of Remote Laboratories that allows the development of practices of laboratories of Control Engineering. The proposed system allows the identification of systems, tuning of controllers and the execution of practices in real devices. It also allows a set of reports on the phenomena analyzed in each practice. A survey is applied to measure the level of satisfaction of the users with respect to the proposal developed through the Iadov technique, obtaining a high level of satisfaction.